Identification of sources of resistance to Phoma medicaginis isolates in Medicago truncatula SARDI core collection accessions, and multigene differentiation of isolates - Ellwood, Simon; Kamphuis, L.; Oliver, Richard (2006)
Phoma medicaginis is a necrotrophic fungal pathogen, commonly found infecting the annual medic Medicago truncatula. To differentiate eight P. medicaginis isolates, five gene regions were examined: actin, β-tubulin, calmodulin, translation elongation factor 1-α (EF-1α), and the internal transcribed spacer ribosomal DNA. Sequence comparisons showed that specimens isolated from M. truncatula in Western Australia formed a group that was consistently different from, but allied to, a P. medicaginis var. medicaginis type specimen. EF-1α contained a hyper-variable 55-bp repeat unit, which forms the basis of a rapid polymerase chain reaction-based method of reliably distinguishing isolates. Characterization of three isolates showed that all exhibited a narrow host range, causing disease only in M. sativa and M. truncatula among eight commonly cultivated legume species sampled. Infection of 86 M. truncatula single-seeded accessions showed a continuous distribution in disease phenotypes, with the majority of accessions susceptible. On a 1-to-5 disease reaction scale increasing in severity, individual fungal isolates showed means of 2.6 to 3.2, and scores ranged from 1 to 4.8 among accessions. The results presented here suggest that M. truncatula harbors specific and diverse sources of resistance to individual P. medicaginis genotypes.